Technology Status and Development of Wind Power Converters - FENG Jianghua (Kongzhi Yu Xinxi Jishu)
Wind power converter is the critical equipment for wind power generation system, and its performance affects the reliability and stability of the power quality and wind power generation system directly. Starting from the type of wind power converter, this article introduces the current wind power converter topology, application requirements, typical technology status and analyzes the future development trend of technology, which can provide reference for the technology development of wind power converter and its industrial planning.